THE EFFECT OF GIVING GOAT MANURE FERTILIZER WITH DIFFERENT DOSES AND FREQUENCIES ON GROWTH AND YIELD OF Calliandra calothyrsus PLANTS - ., Syamhaji; Trisnadewi, A. A. A. .S.; Duarsa, M. A. P. (Jurnal Peternakan Tropika, 2024)
One of the steps to overcome the limitation of forage is to utilize plants that have high nutrient content and are responsive to fertilization, namely the Calliandra calothyrsus plant. Goat manure can be an alternative because it contains 0.60% nitrogen, 0.30% phosphorus, 0.17% potassium and 60% air, which is expected to increase the production of Calliandra calothyrsus . The study aimed to determine the effect of application of goat manure fertilizer with different doses and frequencies and its interaction on the growth and yield of Calliandra calothyrsus plants. The research used a completely randomized design (CRD) with a factorial pattern with two factors. The first factor was the frequency of fertilizer application consisted of F1 = 1 time, F2 = 2 times and F3 = 3 times. The second factor was the fertilizer dosage consisted of D0 = 0 tons ha -1 , D10 = 10 tons ha -1 , D20 = 20 tons ha -1 and D30 = 30 tons ha -1 so that there were 12 experimental units and each unit repeated 4 times so 48 experimental units are needed. The variables observed were growth, yield and growth characteristics variables. The results of the research showed that there was no interaction between the dose and frequency of goat manure fertilizer on all observation variables. application a dose of 30 tons ha -1 of goat manure fertilizer and 3 times the frequency of giving fertilizer tended to give the highest results on the growth, yield and characteristics variables of Calliandra calothyrsus plants. The conclusion of the research that there was no interaction between frequency and dose, a dose of 30 tons ha -1 of goat manure fertilizer and 3 times the frequency of fertilizer application tended to give the highest results on the growth, yield and characteristics variables of Calliandra calothyrsus plants.